Extra digital glomangioma - Rao A; Indira D; Kamal J (Wolters Kluwer Medknow Publications, 2010)
Glomus tumors are relatively rare vascular tumors with reported incidence of 1.6% of all soft tissue tumors. It is variously regarded as a hamartoma or a neoplasm of neuromyoarterial glomus, which consists of dilated vascular channels, surrounded by proliferating glomus, nerve cells, and plays an important role in temperature regulation. We report the case of glomangioma in a 43-year-old male who came to dermatology OPD with a painful lesion over the right elbow of six months duration. Cutaneous examination revealed a single round reddish blue papule of about 0.5 cm in size on the flexor aspect of the right elbow. The papule was firm in consistency and tender. The excision biopsy showed stratified squamous lining with well circumscribed tumor in the dermis. The tumor consisted of sheets of uniform cells with pale cytoplasm; round to ovoid centrally placed punched out nuclei and well defined cell margins. There were numerous dilated thin walled vascular spaces surrounded by a layer of tumor cells and the histopathology was consistent with glomangioma.